Ursolic Acid Reverses the Chemoresistance of Breast Cancer Cells to Paclitaxel by Targeting MiRNA-149-5p/MyD88 - Xiang, Fenfen; Fan, Yan; Ni, Zhenhua; Liu, Qiaoli; Zhu, Zhaowei; Chen, Zixi; Hao, Wenbin; Yue, Honghong; Wu, Rong; Kang, Xiangdong (Frontiers in Oncology, 2019)
Paclitaxel (PTX) is widely used as a front-line chemotherapy for breast cancer treatment. However, its clinical applications are limited by the development of chemoresistance. The objective of this study was to investigate the reversal effects of ursolic acid (UA) on PTX resistance and the possible mechanisms in breast cancer. The role of miRNA-149-5p/MyD88 in the regulation of PTX resistance was investigated by the transfection of breast cancer cells with MDA-MB-231 (231) and MDA-MB-231/PTX-resistance (231/PTX) with lentiviruses carrying the MyD88 gene, shRNA specific for MyD88, the miR-149-5p gene and shRNA specific for. The PTX sensitivity was assessed by a CCK-8 assay. qRT-PCR and Western blot analyses were used to detect changes in the mRNA and protein levels. Flow cytometry was used to measure the rate of cell apoptosis. A luciferase activity assay was used to detect the binding site of miR-149-5p on the 3’UTR of MyD88. 231/PTX cells were injected into the flanks of female athymic nude mice, and the mice were randomly divided into the 5 following groups: PBS, PTX (low), PTX (high), UA and PTX+UA. Our data show that UA reversed the resistance of breast cancer 231/PTX cells to PTX in vitro and in vivo. UA treatment significantly increased the expression of miR-149-5p, which was lower in 231/PTX cells than it was in 231 cells. Furthermore, the overexpression of miR-149-5p increased the sensitivity of 231/PTX cells to PTX treatment, whereas the knockdown of the miR-149-5p gene attenuated the effects of UA on the regulation of PTX sensitivity. A luciferase assay demonstrated that miR-149-5p could directly regulate the transcriptional activity of MyD88, a known PTX-resistance gene, by targeting the 3’UTR of MyD88. Meanwhile, the downregulation of MyD88 through the overexpression of miR-149-5p or UA treatment inhibited the activation of the Akt signaling pathway in 231/PTX cells. Thus, our data indicate that UA can reverse PTX resistance by targeting the miRNA-149-5p/MyD88 axis in breast cancer cells.